Saber local e saber pretensamente universal, no contexto da globalização - José Marín (Ciências Sociais Unisinos, 2007)
The big challenge that globalization as a process of cultural domination poses to education forces us to reflect on the kind of education needed in every local context. By education we mean a cultural process of transmission of wordviews, value systems and forms of knowledge. As globalization does not respect neither biodiversity nor cultural diversity, it distorts the real and symbolic references of local contexts. Thus the present challenge to be taken up by education vis-à-vis such a context is to build, on the basis of an intercultural reflection, a kind of education that values and respects biodiversity and cultural diversity with a view to envisioning a project of a viable society. Education must promote a system of values and respect each ecological and historical context. It must value local cultures, languages and forms of knowledge, adjusting to the needs, potentials and limitations of each local reality within the global context.